Para todos tiene la muerte una mirada - Mampaso, Ana (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
Reflexions about the pass of time and old age in human being, the body, the loneliness and the memory, by 14 photografers, 11 men and 3 women, thats confronts face to face to this cuestion. Every artist that look for the beauty and truth in the last chapter of theri lifes, in difents ways, some times in a direct way, and, others, in revindicative one., hilarious or imaginative, but always with grate courage and sense of tenderness and compression.